The Undergraduate Teaching Assistant Experience Offers Opportunities Similar to the Undergraduate Research Experience - Kelly A. Schalk (American Society for Microbiology, 2009)
There has been a growing concern in higher education about our failure to produce scientifically trained workers and scientifically literate citizens. Active-learning and research-oriented activities are posited as ways to give students a deeper understanding of science. We report on an undergraduate teaching assistant (UTA) experience and suggest that students who participate as a UTA obtain benefits analogous to those who participate as an undergraduate research assistant (URA). We examined the experiences of 24 undergraduates acting as UTAs in a general microbiology course. Self-reported gains by the UTAs were supported by observational data from undergraduates in the course who were mentored by the UTAs and by the graduate teaching assistants (GTAs) with whom the UTAs worked. Specifically, data from the UTAs’ journals and self-reported Likert scales and rubrics indicated that our teaching assistants developed professional characteristics such as self-confidence and communication and leadership skills, while they acquired knowledge of microbiology content and laboratory skills. Data from the undergraduate Likert scale as well as the pre- and post-GTA rubrics further confirmed our UTA’s data interpretations. These findings are significant because they offer empirical data to support the suggestion that the UTA experience is an effective option for developing skills and knowledge in undergraduates that are essential for careers in science. The UTA experience provides a valuable alternative to the URA experience.